Photocatalytic degradation and mineralization of amoxicillin and ofloxacin using TiO2-SiO2 composites. Issue 2 (7th February 2021) - Rani, Sonam; Garg, Alok; Singh, Neetu
Abstract: TiO2 -SiO2 mixed oxides in ratios between 20:80 and 80:20 have been prepared using a sol-gel method. To make full use of catalysis, optimization conditions such as SiO2 content, solution pH, and catalyst loading were investigated. The photocatalysts were characterized spectroscopically as nanoparticles of small crystallite size. Their efficiency for UV-A light induced photocatalytic degradation of amoxicillin and ofloxacin was evaluated, with 80% TiO2 -20% SiO2 being the most active, resulting in complete mineralization and non-toxicity. The catalyst shows some recyclability up to the seventh cycle.